Physiological and Biochemical Aspects of Soybean Sprayed with Manganese Phosphite for the White Mold Control - Novaes, Maria Izabel Costa (2016)
Considering the importance of white mold, caused by Sclerotinia sclerotiorum, to decrease soybean yield, new alternatives for disease control need to be investigated. The present study aimed to determine the potential of the manganese (Mn) phosphite in helping soybean plants to counteract S. sclerotiorum by examining the photosynthetic performance (leaf gas exchange and chlorophyll (Chl) a fluorescence parameters), the participation of defense enzymes (β-1,3- glucanases (GLU), phenylalanine ammonia-lyase (PAL) and polyphenoloxidases (PPO)) as well as those related to the antioxidant metabolism (superoxide dismutase (SOD), catalase (CAT), peroxidase (POX) and ascorbate peroxidase (APX)) and the concentrations of hydrogen peroxide (H 2 O 2 ), superoxide (O 2- ) and malondialdehyde (MDA). White mold severity was significantly reduced on plants sprayed with Mn phosphite which showed a better preservation of the functionality of the photosynthetic apparatus based on the values of the leaf gas exchange and Chl a fluorescence parameters. The SOD, CAT, POX and APX activities increased for inoculated plants non-sprayed with Mn phosphite in comparison to inoculated plants sprayed with this product. The GLU and PAL activities for inoculated plants sprayed with Mn phosphite were greater and contributed to reduce the white mold severity. In conclusion, the present study brings novel evidence of the potential of Mn phosphite to control white mold at both biochemical and physiological levels.